Estimation of IDF curves of extreme rainfall by simple scaling in Slovakia - BARA, Márta; KOHNOVÁ, Silvia; GAÁL, Ladislav; SZOLGAY, Ján; HLAVČOVÁ, Kamila (Contributions to Geophysics and Geodesy, 2009)
Scaling properties of the short  term extreme rainfall  has not been investigated so far  in  Slovakia.    In  this  study  the simple  scaling  theory  is applied  to the intensity- duration-frequency  (IDF) characteristics  of short duration  rainfall.   The  rainfall   data for  the analysis   consists  of rainfall   intensities  of durations ranging   from  5 minutes  to 180 minutes and daily rainfall  amounts for 55 stations from the whole territory of Slovakia, respectively, taken from the historical dataset of Šamaj and  Valovič (1973)  and  from the database of the  Slovak  Hydrometeorological Institute  (SHMI).  The  scaling  behaviour of rainfall  intensities  was  examined and  it was  shown  that for time  scaling,  the statistical properties of rainfall  follow the hypothesis of simple  scaling.  The  scaling  exponents were derived  in all the analysed stations. In the selected  test stations, the inﬂuence of excluding the 5 min duration on the derived  IDF curves was also examined. The possibility of using wide sense simple  scaling  in Slovakia  was demonstrated.